Mediation: standards of conduct - Ahmad, Muhamad Hassan; Eishan Jan, Mohammad Naqib; Nafees, Seeni Mohamed (CLJ Publication, 2020)
In conducting an effective mediation, the standards of conduct of mediators in the process, inter alia, play a pivotal role. In Malaysia, the Mediation Act 2012 (‘Act’) was enacted with the intention to: “promote and encourage mediation as a method of alternative dispute resolution by providing for the process of mediation, thereby facilitating the parties in disputes to settle disputes in a fair, speedy and cost-effective manner and to provide for related matters”. The Act defines ‘mediation’ as: “a voluntary process in which a mediator facilitates communication and negotiation between parties to assist the parties in reaching an agreement regarding a dispute”. It provides some standards of conduct for mediators but these standards are not sufficient. Therefore, the standards of conduct for mediators prepared by the American Arbitration Association (AAA); the American Bar Association’s Section of Dispute Resolution (ABA); the Association for Conflict Resolution (ACR), i.e., the Model Standards of Conduct for Mediators 2005; and standards of conduct for mediators adopted by the New Jersey Supreme Court, i.e., Standards of Conduct for Mediators in Court-Connected Programs 2000; are also discussed in an extensive manner in this chapter. Basically, there are some well-known standards of conduct for mediators such as self-determination; competence; confidentiality; impartiality; conflicts of interest; quality of the process; fees for service; advertising and solicitation; and advancement of mediation practice.